COMPREHENSIVE PHYTOCHEMICAL MAPPING OF INDIAN FLORA: LC–MS/MS-BASED IDENTIFICATION OF BIOACTIVE METABOLITES - Nath, Sanjeeb Kumar; Das, Sushil (International Journal of Research -GRANTHAALAYAH, 2026)
Indian medicinal plants constitute a rich source of structurally diverse bioactive metabolites with significant therapeutic relevance. Advances in analytical technologies, particularly liquid chromatography–tandem mass spectrometry (LC–MS/MS), have greatly enhanced the identification and characterization of complex phytochemical profiles. This review critically summarizes published literature on LC–MS/MS-based phytochemical investigations of Indian medicinal plants, focusing on the identification of major classes of secondary metabolites, including flavonoids, alkaloids, phenolic acids, terpenoids, glycosides, and saponins. Evidence from multiple studies demonstrates that LC–MS/MS enables high-resolution metabolite annotation and provides molecular-level insights that support traditional medicinal applications. The review highlights the role of metabolomics-driven approaches in linking ethnopharmacological knowledge with chemical evidence and discusses their significance in drug discovery, quality control, and standardization of herbal formulations.